Disparate and shared transcriptomic signatures associated with cortical atrophy in genetic behavioral variant frontotemporal degeneration - Ting Shen; Jacob W. Vogel; Vivianna M. Van Deerlin; EunRan Suh; Laynie Dratch; Jeffrey S. Phillips; Lauren Massimo; Edward B. Lee; David J. Irwin; Corey T. McMillan (Molecular Neurodegeneration)
Abstract Background Cortical atrophy is a common manifestation in behavioral variant frontotemporal degeneration (bvFTD), exhibiting spatial heterogeneity across various genetic subgroups, which may be driven by distinct biological mechanisms. Methods We employed an integrative imaging transcriptomics approach to identify both disparate and shared transcriptomic signatures associated with cortical thickness in bvFTD with C9orf72 repeat expansions or pathogenic variants in GRN or MAPT. Functional enrichment analyses were conducted on each gene list significantly associated with cortical thickness. Additionally, we mapped neurotransmitter receptor/transporter density maps to the cortical thickness maps, to uncover different correlation patterns for each genetic form. Furthermore, we examined whether the identified genes were enriched for pathology-related genes by using previously identified genes linked to TDP-43 positive neurons and genes associated with tau pathology. Results For each genetic form of bvFTD, we identified cortical thickness signatures and gene sets associated with them. The cortical thickness associated genes for GRN-bvFTD were significantly involved in neurotransmitter system and circadian entrainment. The different patterns of spatial correlations between synaptic density and cortical thinning, further confirmed the critical role of neurotransmission and synaptic signaling in shaping brain structure, especially in the GRN-bvFTD group. Furthermore, we observed significant overlap between genes linked to TDP-43 pathology and the gene sets associated with cortical thickness in C9orf72-bvFTD and GRN-bvFTD but not the MAPT-bvFTD group providing specificity for our associations. C9orf72-bvFTD and GRN-bvFTD also shared genes displaying consistent directionality, with those exhibiting either positive or negative correlations with cortical thickness in C9orf72-bvFTD showing the same direction (positive or negative) in GRN-bvFTD. MAPT-bvFTD displayed more pronounced differences in transcriptomic signatures compared to the other two genetic forms. The genes that exhibited significantly positive or negative correlations with cortical thickness in MAPT-bvFTD showed opposing directionality in C9orf72-bvFTD and GRN-bvFTD. Conclusions Overall, this integrative transcriptomic approach identified several new shared and disparate genes associated with regional vulnerability with increased biological interpretation including overlap with synaptic density maps and pathologically-specific gene expression. These findings illuminated the intricate molecular underpinnings contributing to the heterogeneous nature of disease distribution in bvFTD with distinct genetic backgrounds.